Teaching written foreign language communication in a nonlinguistic university - Zara Mukhamcherievna Shadzhe (Вестник Майкопского государственного технологического университета, 2023)
The article discusses the problem of effective written foreign language communication teaching, substantiates the need to develop a methodology for teaching written foreign language communication in a nonlinguistic university. The relevance of the research is due to the high interest of employers in employees possessing foreign language business discourse skills. Business writing skills are one of the factors for a young specialist’s success. The study of the issue of training competent specialists remains in the problem field of teaching written foreign language communication in a nonlinguistic university. The problem of teaching foreign language writing was touched upon, however, the task of teaching foreign language discourse remains relevant in a nonlinguistic university and requires resolution of the contradiction between the need for specialists with written foreign language communicative competence and the development of the issue of teaching written foreign language communication in a nonlinguistic university. The purpose of the research is to develop a methodology for the development of written foreign language communicative competence in a foreign language practical lessons in a nonlinguistic university. In the course of the research the literature on the topic has been analyzed, the methods of observation and comparison have been used, and a pedagogical experiment has been carried out. The research results are of practical importance. They can be used by foreign language teachers in a nonlinguistic university in teaching «Professional foreign language», «Business foreign language», «Foreign language for professional communication», «Foreign language for business professional communication», «Foreign language in the professional sphere», «Technical foreign language», «Foreign language in the field of professional activity», «Foreign language for the profile of training». The study has showed that teaching written business discourse will be more successful if the learning process is based on a communicative-cognitive approach, the content of educational materials is situational, and an effective control system is developed.